Recognising Stakeholder Conflict and Encouraging Consensus of ‘Science-Based Management’ Approaches for Marine Biodiversity Beyond National Jurisdiction (BBNJ) - Gaebel, Christine; Baulcomb, Corinne; Johnson, David E.; Roberts, J. Murray (Frontiers in Marine Science, 2020)
Areas beyond national jurisdiction (ABNJ) encompass the seabed, subsoil and water column beyond coastal state jurisdiction. From providing sustenance and supporting livelihoods, to absorbing anthropogenic carbon dioxide emissions, ABNJ ecosystems are vital to the wellbeing of humankind. However, an enhanced understanding of marine biodiversity beyond national jurisdiction (BBNJ) and its significance has not equated to its successful conservation and sustainable use. Negotiations for a new international legally binding instrument for the conservation and sustainable use of BBNJ have scoped applicable principles for a future agreement, including the use of best available science and science-based approaches. However, there remains a lack of convergence on what science-based approaches would look like, or how they would be operationalised. In order to negotiate and implement a meaningful BBNJ treaty that can meet conservation and sustainable use objectives, stakeholder perceptions must be identified, and areas of divergence must be overcome. This study uses Q-methodology to reveal and analyse the diversity of perceptions that exist amongst key stakeholders regarding what it means to operationalise science-based approaches for the conservation and sustainable use of BBNJ. The Q-study features 25 stakeholder interviews and 30 Q-study participants revealing four different perceptions, each of which represent a different interpretation of what science-based management means in the context of BBNJ. Across these perceptions, there were areas of stakeholder consensus (e.g. regarding the benefits of integrative management, the application of precautionary approaches when data are insufficient, and the issues pertaining to the trustworthiness and credibility of science) and areas of stakeholder conflict (e.g. regarding the definition, function and authority of science within current and future BBNJ governance processes). Key implications of this study include the evidencing of fundamental tensions between differing perceptions of the authority of science and between conservation and sustainable use objectives, that may be fueling stakeholder conflict, and the subsequent proposal of integrative and highly participatory management approaches to operationalise science-based management of BBNJ.